Scammarctus batei Holthuis 2002, n. comb. - Holthuis, Lipke B. (Zenodo, 2002)
Scammarctus batei (Holthuis, 1946) n. comb. (Figs 9-11; 66D, E) Scyllarus batei Holthuis, 1946: 94; 1984: Scylr.2, fig.; 1991: 219, figs 415, 416. — Estampador 1959: 40. — Robertson 1968: 334. — Prasad & Tampi 1969: 82. — Burukovsky 1974: 107; 1983: 151. — Prasad et al. 1980: 89, fig. 12. — Prasad 1983: 144, fig. 3c. — Chan & Yu 1986: 155, pl. 4, pl. 9 figs A, B; 1993: 205, col. fig. — Sekiguchi 1986a: 1290; 1987a: 331; 1987b: 415, 417. — Huang 1994: 564. Arctus orientalis Bate, 1888: 68, pl. 9 fig. 4. — Alcock & Anderson 1894: 165. — Alcock 1901: 181. — Lloyd 1907: 6. — Estampador 1937: 495 [non Scyllarus orientalis Lund, 1792 (= Thenus orientalis )]. Scyllarus orientalis – De Man 1916: 73. — Ramadan 1938: 126, fig. 2. — Sewell 1955: 200, 201, 203. Scyllarus batei batei – Holthuis 1960: 149. — George 1969: 433. — Phillips et al. 1980: 69. Scyllarus batei arabicus Holthuis, 1960: 149. — George 1969: 434. — Phillips et al. 1980: 69. — Fransen et al. 1998: 66. TYPE MATERIAL. — Syntypes: RV Challenger , stn 209, 2 specimens (BM), primarily identified as Arctus orientalis . TYPE LOCALITY. — Philippines, between Bohol and Cebu, at 10°14’N, 123°54’E, depth 174 m. MATERIAL EXAMINED. — Madagascar. RV Vauban , stn CH 44, 15°25.7’S, 46°01.0’E, 200-210 m, 7.XI.1972, 1 badly damaged c. 12 mm (MNHN-Pa 572). — Stn CH 93, 22°17.3’S, 43°05.9’E, 350 m, 27.XI.1973, 1 (MNHN-Pa 568). Mozambique. RV Prof. Mesyatsev , stn 66, 24°57.0’S, 35°07.1’E, 200-210 m, 25.I.1976, 2 (VNIRO). — RV Anton Bruun , cruise 8, stn 397A, 25°12’S, 34°04’E, shrimp trawl, 230-295 m, 29.IX.1964, 3 24- 30 mm, 1 25 mm (USNM). — RV Prof. Mesyatsev , stn 94, 25°31.8’S, 34°49.8’E, 220-225 m, 3.II.1976, 2, 2 (VNIRO). Kenya. RV Anton Bruun , cruise 8, stn 421G, 2°56’S, 40°28’E, shrimp trawl, 240 m, 8.XI.1964, 2 25 and 35 mm, 2 18 and 31 mm (USNM). — RV Fridtjof Nansen , stn 862, 3°26’S, 40°23’E, 484 m, 1 (RMNH D 33223). — RV Manihine cruise 377, stn 16, 3°08’S, 40°20.5’E- 3°7.5’S, 40°21’E, 250-255 m, muddy sand, Agassiz trawl, 5.IX.1974, A. J. Bruce ...